ANALYSIS OF DETERMINING FACTORY LOCATION OF CONSUMER GOODS COMPANY - Buhori, Buhori; Amanina, Adilah Asma; Khatami, Narendra Ahmad (Journal of Digital Business and Innovation Management, 2022)
The location of a business becomes very important because it concerns the efficiency and effectiveness of a business. Manufacturing companies are in dire need of raw materials, labor, and various other input factors, which are easy, fast and precise. The business location must be easily accessible to consumers, known to consumers and make it easier for factory managers to reach the goods to be sold to increase effectiveness; determining the location of the business is not easy, many factors influence the decision in determining the location, because it concerns the company's operational costs. This study aims to determine the factors that are the consideration of a consumer goods company in choosing the current factory location. The study was conducted using primary data and secondary data. The data analysis was carried out using the rating factor method by determining the determinants of location feasibility and the center of gravity method as well as the forecasting method. factors that are taken into consideration in choosing the business location of a consumer good company are availability of labor, availability of electric power, transportation facilities, health, security, and fire prevention services, community attitudes, land and building costs, and possibility of expansion. Factors that are not paid much attention to in determining the business location for the company are: the location of the market, the location of raw materials, residential, educational, shopping, and telecommunication facilities, the area of the parking lot, the sewer, and the width of the road.